Alcohol and condom use among HIV-positive and HIV-negative female sex workers in Nagaland, India. (September 2013) - Nuken, Amenla; Kermode, Michelle; Saggurti, Niranjan; Armstrong, Greg; Medhi, Gajendra Kumar
This study examines the relationship between alcohol use, HIV status, and condom use among female sex workers in Nagaland, India. We analyzed data from a cross-sectional survey undertaken in 2009, using descriptive and multivariate statistics. Out of 417 female sex workers, one-fifth used alcohol daily and one-tenth were HIV-positive. HIV-positive female sex workers were more likely than HIV-negative female sex workers to consume alcohol daily (30.2% vs. 18.0%). HIV-positive daily alcohol users reported lower condom use at last sex with regular clients compared to HIV-positive non-daily alcohol users (46.2% vs. 79.3%), a relationship not evident among HIV-negative female sex workers. There is a need to promote awareness of synergies between alcohol use and HIV, and to screen for problematic alcohol use among female sex workers in order to reduce the spread of HIV.